2011
DOI: 10.1037/a0021613
|View full text |Cite
|
Sign up to set email alerts
|

New rule use drives the relation between working memory capacity and Raven's Advanced Progressive Matrices.

Abstract: The correlation between individual differences in working memory capacity and performance on the Raven's Advanced Progressive Matrices (RAPM) is well documented yet poorly understood. The present work proposes a new explanation: that the need to use a new combination of rules on RAPM problems drives the relation between performance and working memory capacity scores. Evidence for this account is supported by an item-based analysis of performance during standard administration of the RAPM and an experiment that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
116
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(139 citation statements)
references
References 29 publications
15
116
8
Order By: Relevance
“…Arguably, the sheer amount of elements and rules that need to be handled while solving an item would exceed the storage capacity of working memory. Still, working memory capacity has not been assessed directly in these studies and, to the contrary, several studies that have assessed working memory capacity have failed to find a relation with item difficulty (Salthouse & Pink, 2008;Unsworth & Engle, 2005;Wiley, Jarosz, Cushen, & Colflesh, 2011). For example, Unsworth and Engle (2005) showed that item difficulty is not at all related to working memory capacity.…”
Section: The Role Of Working Memory Capacity In Rapmmentioning
confidence: 87%
“…Arguably, the sheer amount of elements and rules that need to be handled while solving an item would exceed the storage capacity of working memory. Still, working memory capacity has not been assessed directly in these studies and, to the contrary, several studies that have assessed working memory capacity have failed to find a relation with item difficulty (Salthouse & Pink, 2008;Unsworth & Engle, 2005;Wiley, Jarosz, Cushen, & Colflesh, 2011). For example, Unsworth and Engle (2005) showed that item difficulty is not at all related to working memory capacity.…”
Section: The Role Of Working Memory Capacity In Rapmmentioning
confidence: 87%
“…The involvement of WMC is particularly high when more cues need to be considered or more complex rules need to be abstracted (Karlsson, Juslin, & Olsson 2008;Mata et al, 2012). WMC is also associated with accuracy in a prototypical rule-induction task-Raven's Progressive Matrices-particularly for items requiring complex rules (D. R. Little, Lewandowsky, & Craig, 2014;Wiley, Jarosz, Cushen, & Colflesh, 2011). Despite these compelling connections, there is only one study directly assessing how WMC affects the prediction of continuous processes: McDaniel et al (2014) suspected that higher WMC allows participants to actively maintain a range of cue-criterion values and to concurrently compare them over trials to abstract a functional rule.…”
Section: Nonlinear Dynamic Processesmentioning
confidence: 99%
“…It is also highly predictive of professional and educational success (Gottfredson, 1997) and has, therefore, been a prime target of intervention. One of the core processes driving Gf, as well as other higher cognitive abilities, is WM (Wiley, Jarosz, Cushen, & Colflesh, 2011). Estimates report a shared variance of at least 50% (Kane, Hambrick, & Conway, 2005;Oberauer, Schulze, Wilhelm, & Suss, 2005), and neuroimaging evidence has demonstrated functional overlap in the lateral prefrontal and parietal cortices, implicating shared neural resources that underlie both constructs (Burgess, Gray, Conway, & Braver, 2011).…”
Section: Introductionmentioning
confidence: 99%